Content of Amino Acids in Maize and Yellow Lupine after Fluorine Application to Soil - Radosław Szostek; Zdzisław Ciećko; Elżbieta Rolka; Mirosław Wyszkowski (Agriculture, 2021)
Pollution of the natural environment with fluorine compounds makes the continuous monitoring of the content of this element necessary, not only in the air, water and soil, but also in food. A high level of fluorine contamination of soils can affect quality of the obtained yields, affecting the amino acid composition of protein. It often becomes a cause of reducing nutrition and feed value of agricultural yields. In the undertaken studies, the influence of fluorine application to the soil on the amino acid content in proteins accumulated in the above-ground parts (aerial) of Zea mays L. and Lupinus luteus L. was studied. The lowest and medium doses of fluorine had a significant positive effect on the content of exogenous and endogenous amino acids in the protein of the aerial mass of maize, for which the increase of sum of all amino acids was 7% and 8%, respectively, in relation to controls. The above-ground parts of yellow lupine were characterised by a much higher content of the tested amino acids than maize. The subsequent influence of soil contamination with fluorine on the amino acid content in yellow lupine did not have the same effect as in the main plant, and the influence of fluorine was somewhat limited. With respect to yellow lupine, it was demonstrated that the lowest fluorine dose (100 mg F kg−1 of soil), did not have a beneficial influence on the sum of all amino acids. The medium and highest doses of fluorine depressed in a small degree the content of the sum of these compounds in the dry mass of yellow lupine.